PENERAPAN MEDIA PEMBELAJARANMOODLEUNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN TEKNOLOGI PERKANTORAN PADA SISWA KELAS X OTKP SMK NEGERI 1 WONOGIRI - Widya Ajeng Mutia Pratami; C. Dyah Sulistyaningrum I; Patni Ninghardjanti (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
The purpose of this study was to determine the application of MOODLE learning media can improve learning outcomes in office technology subjects in class X OTKP SMK Negeri 1 Wonogiri.This research is a Classroom Action Research (PTK) which is carried out in two cylces with stages consisting of planning, implementing, acting, observing, and reflecting. The research subjects were students of class X OTKP 2 SMK Negeri 1 Wonogiri, totaling 36 students. Types of data include primary data, namely data directly obtained from research subjects, and secondary data, namely supporting data in the form of books, documents, and archives. Sources of data include informants, namely students, the place is SMK Negeri 1 Wonogiri and the event is the learning media MOODLE, documents and archives, namely syllabus, lesson plans, and assessmet books. Data collection techniques are tests with post test questions, practical questions and non test with observation, interview, questionnaires, and documentation. Data validity techniques using triangulation of sources and methods. Data analysis used critical analysis techniques and comparative descriptive.The results showed that the application of MOODLE learning media can improve learning outcomes in office technology subjects from pre cycle to cycle I, and from cycle I to cycle II. The average cognitive score per cycle increased from 65,97 to 79,31 and 84,03. The average affective value also increased from 67,78 to 76,38 and 84,86. The psychomotor scores increased from70,97 to 79,58 and 84,86. The percentage of pre-cycle completeness is still low, namely the cognitive 30,6%, affective 16,67%, and psychomotor 47,72. A significant increase in learning outcomes occured in the first cycle, namely the cognitive value with a percentage of 77.78% completeness, 66.67% affective, and 69.44% psychomotor although it was still not optimal. The implementation of cycle II causes a very significant increase in learning outcomes, namely the cognitive value with a percentage of 91.67%, affective 86.11%, and psychomotor 91.67% so that learning outcomes are optimal. Keywords: MOODLE learning media, learning outcomes